(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Metformin is a popular oral antidiabetic medicine of the Biguanide class. It is widely chosen as the first line therapy for treating Type 2 Diabetes Mellitus. The drug is believed to be a comparatively safer agent for controlling blood sugar. This case report aims at describing an unusual phenomenon of Metformin hypersensitivity in a female patient who presented with perioral lesions. JCMCTA 2016 ; 27 (1) : 75 - 76